Iodine Consumption and Linear Growth of Children Under Five Years Old in Malabero Coastal Area, Bengkulu City (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
The high prevalence of stunting is influenced by nutritional intake. Iodine is an important micronutrient for growth. Bengkulu City is located along coastal area, hence it has potentially high iodine food sources. However, stunting prevalence was still high. This was a cross-sectional study conducted from March to July 2016 which aimed to determine the relationship between iodine consumption and linear growth of children under five years old in Malabero coastal area of Bengkulu City. The population were children aged 2-5 years old with a sample of 73 children. Measurement of linear growth was based on AHZ index using microtoice with capacity of 200 cm and accuracy of 0.1 cm. Iodine intake was measured based on semiquantitative Food Frequency Questionnaire (FFQ). The results showed that 71.2% of children under five years old did not had sufficient iodine consumption with average percentage of iodine sufficiency 47.7% Â± 0.456. There were 53.5% of children under five years old who experienced stunting. Low iodine consumption was shown to be associated with stunting. There were 73.1% children under five years old with insufficient iodine intake who were stunted while only 4.8% children under five years old with sufficient iodine intake who were stunted.